2020
DOI: 10.3390/jof6020095
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Dermatophytoses in Switzerland According to a Survey of Dermatophytes Isolated in Lausanne between 2001 and 2018

Abstract: Dermatophytes are the most common pathogenic agents of superficial mycoses in humans and animals. Knowledge of their epidemiology can facilitate the prevention of dermatophytosis and improve prophylactic measures. We sought to determine the incidence of the different dermatophyte species diagnosed in Lausanne (Switzerland) from 2001 to 2018. In total, 10,958 dermatophytes were isolated from patients and 459 from pets. Overall, 99% of tinea unguium and tinea pedis were caused by Trichophyton rubrum and Trichoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 32 publications
2
35
0
2
Order By: Relevance
“…Of these, the first seven are known to cause more infections in animals and/or humans. 26,[51][52][53][54] In recent years, there has been an upsurge in the frequency of infection of skin as well as its appendages by non-dermatophyte moulds and yeasts. This can be attributed to the emergence of chronic diseases, such as diabetes, and decline in host immune defence mechanisms by diverse underlying diseases.…”
Section: Ae Ti Olog I C Al Ag Ents For Superfi Cial Mycos E Smentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, the first seven are known to cause more infections in animals and/or humans. 26,[51][52][53][54] In recent years, there has been an upsurge in the frequency of infection of skin as well as its appendages by non-dermatophyte moulds and yeasts. This can be attributed to the emergence of chronic diseases, such as diabetes, and decline in host immune defence mechanisms by diverse underlying diseases.…”
Section: Ae Ti Olog I C Al Ag Ents For Superfi Cial Mycos E Smentioning
confidence: 99%
“…As discussed earlier, at present, nine species of dermatophytes are reported namely Epidermophyton , Trichophyton , Microsporum , Arthroderma , Nannizzia , Ctenomyces , Lophophyton , Guarromyces and Paraphyton . Of these, the first seven are known to cause more infections in animals and/or humans 26,51‐54 . In recent years, there has been an upsurge in the frequency of infection of skin as well as its appendages by non‐dermatophyte moulds and yeasts.…”
Section: Aetiological Agents For Superficial Mycosesmentioning
confidence: 99%
“…Although treatment is available, there are increasing reports of antifungal resistance and tolerance in dermatophytes [ 33 , 94 ]. Trichophyton rubrum is the most predominant dermatophyte species and is the most recurrently described in resistance to standard treatments, followed by T. interdigitale [ 19 ]. Long-term and discontinuing treatments may lead to recalcitrant infections, thus favoring the acquisition of resistance.…”
Section: Treatment Clinical Implications and Perspectivesmentioning
confidence: 99%
“…Tinea capitis, commonly reported in school-age children, is mostly caused by Microsporum canis , Trichophyton tonsurans , Trichophyton violaceum , Trichophyton soudanense , and Microsporum audouinii [ 17 , 18 ]. An epidemiological survey of dermatophytosis in Switzerland from 2001 to 2018 revealed that the main etiological agents isolated from cases of tinea pedis and unguium were T. rubrum and T. interdigitale [ 19 ]. Trichophyton violaceum, T. soudanense, and T. tonsurans were mainly isolated from patients with tinea capitis.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a biological characteristic of dermatophytes is their ability to invade keratin-rich tissues by producing enzymes [3]. Trichophyton rubrum is the commonest causative agent with a diagnosis frequency comparable to the state of a global epidemic [4]. However, the incidence of infections caused by zoophilic dermatophytes T. mentagrophytes [2,5,6] and less common T. verrucosum is increasing in some parts of the world [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%